2001
DOI: 10.1063/1.1416118
|View full text |Cite
|
Sign up to set email alerts
|

An improved method to spot-weld difficult junctions

Abstract: Recent advances in spot-welding technology such as high frequency direct current inverter welders provide an improved and reproducible method to spot-weld difficult junctions. The importance of removing the oxide layers on metal surfaces, accurately delivering the weld pulse profile, and controlling the force applied to the materials during the welding process are discussed in the context of resistance spot-welding a molybdenum crystal to a tantalum loop and attaching a tungstenrhenium thermocouple to the crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…During welding, it was also observed that molten metal expulsion occurred significantly at 0 ms ramp time, whereas there was almost no expulsion taking place at a weld current of 500 A and a ramp time of 8 ms. The upslope, relatively slowly introducing current to the workpieces to be joined, not only minimized the metal expulsion but also reduced the variation in contact resistance between the electrodes and workpieces [13]. Hence, it resulted in a more uniform melting between the faying workpieces and improved the quality of welding of Mo-Re sheet.…”
Section: The Effect Of Ramp Timementioning
confidence: 98%
See 2 more Smart Citations
“…During welding, it was also observed that molten metal expulsion occurred significantly at 0 ms ramp time, whereas there was almost no expulsion taking place at a weld current of 500 A and a ramp time of 8 ms. The upslope, relatively slowly introducing current to the workpieces to be joined, not only minimized the metal expulsion but also reduced the variation in contact resistance between the electrodes and workpieces [13]. Hence, it resulted in a more uniform melting between the faying workpieces and improved the quality of welding of Mo-Re sheet.…”
Section: The Effect Of Ramp Timementioning
confidence: 98%
“…Higher cooling rate could also engender a smaller heat affected zone (HAZ), which is normally the weakest region in weldments, and accordingly benefit the quality of welding [13]. Based on the result, the hold time of 999 ms was set in the next experiments.…”
Section: The Effect Of Hold Timementioning
confidence: 99%
See 1 more Smart Citation
“…The upslope, gradually introducing current to the workpieces to be joined, not only minimized the metal expulsion but also reduced the variation in contact resistance between the electrodes and workpieces. 8 Therefore, it was preferable to use a weld current profile with a ramp time of several milliseconds to improve welding of this alloy. Figure 1 shows the effect of weld time with 8 ms ramp time and other default welding parameters, as shown in Table A.…”
Section: Ramp Timementioning
confidence: 99%
“…On the other hand, high-temperature thermocouples can be firmly attached to difficult samples either mechanically or by means of a spot-welder, 5 and are relatively inert. However, this solution is unsatisfactory because it is necessary to mechanically break and make the contact of the low-temperature thermocouple in situ.…”
mentioning
confidence: 99%